Simultaneous detection of four different neuraminidase types of avian influenza A H5 viruses by multiplex reverse transcription PCR using a GeXP analyser. Issue 2 (March 2016) - Li, Meng; Xie, Zhixun; Xie, Zhiqin; Liu, Jiabo; Xie, Liji; Deng, Xianwen; Luo, Sisi; Fan, Qing; Huang, Li; Huang, Jiaoling; Zhang, Yanfang; Zeng, Tingting; et al.
Abstract : Objectives: In order to develop a multiplex RT‐PCR assay using the GeXP analyser for the simultaneous detection of four different NA serotypes of H5‐subtype AIVs, effective to control and reduce H5 subtype of avian influenza outbreak. Design: Six pairs of primers were designed using conserved and specific sequences of the AIV subtypes H5, N1, N2, N6 and N8 in GenBank. Each gene‐specific primer was fused at the 5′ end to a universal sequence to generate six pairs of chimeric primers, and one pair of universal primers was used for RT‐PCR, and PCR product separation and detection were performed by capillary electrophoresis using the GenomeLab GeXP genetic analysis system. Setting: Single and mixed avian pathogen cDNA/DNA templates were employed to evaluate the specificity of a multiplex assay with a GeXP analyser. Corresponding specific DNA products were amplified for each gene, revealing amplification peaks for M, H5, N1, N2, N6 and N8 genes from four different NA subtypes of influenza A H5 virus. Sample: A total of 180 cloacal swabs were collected from poultry at live bird markets. Main outcome measures: The multiplex PCR assay demonstrated excellent specificity, with each pair of specific primers generating only products corresponding to the target genes and without cross‐amplification with other NA‐subtype influenza viruses or other avian pathogens. Using various premixed ssRNAs containing known AIV target genes, the detection limit for the multiplex assay was determined to be 10 2 copies/μl. The GeXP assay was further evaluated using 180 clinical specimens and compared with RRT‐PCR (real‐time reverse transcriptase PCR) and virus isolation. Conclusions: This GeXP analyser‐based multiplex assay for four different NA subtypes of H5 HPAI viruses is both highly specific and sensitive and can be used as a rapid and direct diagnostic assay for testing clinical samples.